Job satisfaction and conflict among technical employees in selected Malaysian Engineering Firms - Lee, Kum Chee; Chan, Kah Whye (Penerbit Universiti Kebangsaan Malaysia, 1996)
In view of the crucial role of technical workers in the Malaysian workforce,research on their job satisfaction and conflict provides an insight into their distinct sets of norms and values that differ from employees engaged in other professions. The objective of this paper is to identify the factors that affect the job satisfaction of this group of employees through a survey. The results of the survey show that employees in the design department are least satisfied towards each facet of the job while those in the quality control department have the least overall job satisfaction. Similar results are also obtained when the sample is stratified by the various demographic factors. Moreover, intergroup conflict may be negatively related to overall job satisfaction. Engineers in the companies urveyed experienced the lowest level of job satisfaction as compared to the managers and supervisors.